FAKTOR YANG MEMPENGARUHI PENERIMAAN PENDAPATAN ASLI DAERAH PADA DAERAH DENGAN KEMANDIRIAN RENDAH DI PROVINSI BALI - Saktiasa, I Putu Adi; Dewi, Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study was to analyze the effect of GRDP, Total Population, and Number of Tourists simultaneously on the receipt of Regional Original Income in areas that have low independence in the Province of Bali, and to analyze the effect of GRDP, Total Population, and Number of Tourists partially on the receipt of Regional Original Income in areas that have low independence in the Province of Bali. The number of observations in the study were 80 observations. The analysis technique used is panel data regression analysis and multiple linear regression analysis. The software used is Eviews. GRDP, Total Population, and Number of Tourists simultaneously have a positive effect on the receipt of Regional Original Income in areas that have low independence in the Province of Bali. Partially GRDP, Total Population has a positive effect on the acceptance of Regional Original Income in areas that have low independence in the Province of Bali, while the Number of Tourists partially does not have a significant effect on the receipt of Regional Original Income in regions that have low independence in the Province of Bali.